Comparison of one and two-day bowel preparation with polyethylene glycol in pediatric colonoscopy - Najafi, Mehri; Fallahi, Gholam Hossein; Motamed, Farzaneh; Farahmand, Fatemeh; Khodadad, Ahmad; Ghajarzadeh, Mahsa; Rezaei, Nima; Mehrabani, Sanaz (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Proper colon preparation in children has been a challenge for many years. Different regimens have been used for this purpose, but the best regimen is not determined. The aim of this study was to evaluate successful colon preparation before colonoscopy in children who were treated with one- or two-day regimen with polyethylene glycol (PEG) plus bisacodyl and clear liquids. Materials and Methods: In this randomized clinical trial, 100 children (2-14 years old) who were candidates for colonoscopy were enrolled and divided into two groups. The children in group one were started on 2 g/kg PEG powder (17 g in 240 mL water or another beverage) and 5 mg bisacodyl suppository (BD) the day before colonoscopy, whereas those in the other group were started on 1.5 g/kg PEG with fruit juices for two days and 5 mg bisacodyl suppository (BD) for two days before colonoscopy. Results: Compliance rates, regimens, adverse effects, and complete colonoscopy were not significantly different between the two groups. The Boston score was excellent and good in 70% of group one and 72% of group two children, respectively. Compliance rate, adverse effects, and need for enema were similar in both groups. The rate of compliance and non-requirement of enema were significantly higher in children with satisfactory colon preparation. Conclusion: The one-day PEG plus bisacodyl regimen for bowel preparation is as effective as the two-day regimen in children; furthermore, it is well tolerated and has low adverse effects.